Correlates of asthma morbidity in primary care. Issue 6823 (8th February 1992) - Jones, K. P.; Bain, D. J.; Middleton, M.; Mullee, M. A.
Abstract : OBJECTIVES–To explore the morbidity of patients diagnosed as asthmatic in general practice, to examine the determinants of this morbidity, and to derive a simple morbidity screening tool for use in primary care. DESIGN–Patient interviews, lung function measurements, and data extraction from general practice case notes. SUBJECTS–300 asthmatic patients aged 5 to 65 years randomly selected from the repeat prescribing registers of three general practices in the Southampton area. MAIN OUTCOME MEASURES–Reported morbidity using a calculated index based on three questions (Are you in a wheezy or asthmatic condition at least once per week; Have you had time off work or school in the past year because of your asthma; Do you suffer from attacks of wheezing during the night?); mean forced expiratory volume in one second and mean peak expiratory flow (over a seven day period); diurnal variation in peak flow; and the relation of the morbidity index to lung function. RESULTS–Mean forced expiratory volume in one second was 67% predicted (SD 18.4), mean peak expiratory flow was 80% predicted (SD 18.9), and mean diurnal variation was 10% (SD 7.7). 76 subjects were classified as having low morbidity, 95 medium, and 125 high. The morbidity index was significantly associated with forced expiratory volume in one second, mean peak expiratory flow rate, and diurnal variation (p less than 0.05); it was not significantly associated with inhaler technique or use of prophylaxis. CONCLUSIONS–There was a large burden of persisting morbidity across all ages of patients diagnosed as asthmatic in the three well resourced practices studied. The use of the morbidity index may help to target the asthmatic patients needing more attention by concentrating on those reporting medium to high morbidity.